Kepemilikan Institusional Terhadap Tax Avoidance: Peran Moderasi Kinerja Laba - Anisah Novi Karunia; Adelia Puspa Nagari; Alfiana Irsyanti (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2024)
This research tests whether the type of institutional ownership influences tax avoidance practices carried out by an agency with the profitability variable (ROA) as a moderator. Then, this research further tests whether state-owned (government) or privately owned (non-government) companies have more potential for tax avoidance. This research involved 59 manufacturing companies listed on the Indonesia Stock Exchange (BEI) and companies included in the BUMN-20 Index during the 2016-2018 period. The purposive sampling method was used to determine the sample, using four specific criteria. Research data was obtained from annual reports taken from the IDX website and each company's website. The analysis utilized a multiple regression model with SPSS version 25 software to evaluate the strength and direction of the association among the dependent variable, moderating variable, and independent variables. This research shows the results of the relationship between institutional ownership and tax avoidance which is moderated by ROA and there are indications that government companies have more potential to practice tax avoidance.